2004
DOI: 10.1177/154193120404800301
|View full text |Cite
|
Sign up to set email alerts
|

Human in the Loop Evaluation of a Mixed-Initiative System for Planning and Control of Multiple UAV Teams

Abstract: This paper describes a ‘Human in the Loop' evaluation of an early prototype mixed-initiative control system that generated plans for single operator supervision of multiple unmanned aerial vehicles (UAV) missions. The objectives of the evaluation were to assess to what extent human operators were able to understand the plans generated by the automated controllers as well as to point to additional support requirements to drive further development of mixed-initiative planning systems. Six former fighter pilots s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Willems and Heiney (2002) stated that "As errors involving automation tend to be more cataclysmic and costly, the human interface has become more important than ever" (p. 3). The HSIs typically provide insufficient information about automation's goals, current activities, and performance (Liu, Nakata & Furuta, 2004;Lee & See, 2004;Parasuraman & Riley, 1997;Roth et al, 2004;Rook & McDonnell, 1993).…”
Section: Degraded Automation/control and Communication Subsystemsmentioning
confidence: 99%
“…Willems and Heiney (2002) stated that "As errors involving automation tend to be more cataclysmic and costly, the human interface has become more important than ever" (p. 3). The HSIs typically provide insufficient information about automation's goals, current activities, and performance (Liu, Nakata & Furuta, 2004;Lee & See, 2004;Parasuraman & Riley, 1997;Roth et al, 2004;Rook & McDonnell, 1993).…”
Section: Degraded Automation/control and Communication Subsystemsmentioning
confidence: 99%
“…For example, Emilie Roth and her colleagues describe an "intent matrix" interface for specifying a target class's relative value to a modelbased architecture. 4 In this architecture, the operator could select particular targets only indirectly by changing class values and computing new plans until one was found that included a desired target.…”
Section: Coordination Technologymentioning
confidence: 99%
“…However, high LOAs are prone to a loss of situational awareness and complacency by removing the operator from the task [5]. Also, operators often do not understand what autonomous systems are doing because the action selection algorithm is markedly different [6]. As a result, operators are more likely to intervene because they do not trust the system [7].…”
Section: Introductionmentioning
confidence: 99%
“…Exocentric views most often show an overhead view of a map with the positions and status of the robots [13], [14]. In addition to the current state, some interfaces also provide the future state of the robots by displaying the planned routes of the robots [6], [7], target or hazard locations [8], [15] and explored areas of the map [16]. The interface in [17] provided the explored area as well as the open regions around the robots and information about the selected robot's local situation.…”
Section: Introductionmentioning
confidence: 99%